EFISIENSI PASAR MODAL INDONESIA PADA TAHUN PEMILU 2019 - Pratama, Gilang (Jurnal Ekonomi : Journal of Economic, 2019)
This research uses semi-strong efficiency market hypothesis (EMH) methodology to investigate the efficiency market stock price reaction to national political events, Indonesia’s PEMILU 2019. The research is necessary for the reason that if stock price does not instantaneously and fully reflect relevant available information’s, it will be able to mislead economic decisions. The analysis uses a daily adjusted close price of Index Harga Saham Gabungan (IHSG) as sample to representative Bursa Efek Indoneia (BEI). The hypothesis of this research is: (I) Indonesia’s Capital Market is Efficient before and during national election period, and (2) Indonesia’s capital market efficiency is different during National Election Period. The first hypothesis is tested by using probability value which are based on randomness test (Random Walk Method) and serial correlation test. Randomness test is used because one of the characteristics of the efficient market is that prices change randomly, while the serial correlation test is interrelated with the other characteristic of the efficient capital market, that the change of security prices has no correlation to each other. The second hypothesis is tested by using Wilcoxon's signed rank test. From the statistical analysis found that first and second hypothesis is accepted. Limitation of this research parameter used only one Index with daily secondary-data get from the adjusted close price.Keywords: Efficiency, weak-form, randomness, decisions.